C:N:P stoichiometric characteristics and seasonal dynamics of leaf-root-litter-soil in plantations on the loess plateau - Ruosha Liu (Elsevier, 2021)
Ecological stoichiometry is an effective tool for analyzing and explaining changes and connections between plants and the environment. However, the changes in ecological stoichiometry throughout the leaf-root-litter-soil continuum during different seasons in plantation ecosystems are not fully understood. In this study, the C, N and P contents of leaves, roots, litter and soil were measured in four plantations growing Larix principis-rupprechtii, Picea crassifolia, Betula platyphylla and Populus cathayana in spring, summer and autumn. The stoichiometric characteristics and seasonal dynamics along the continuum were analyzed to reveal nutrient limitations on the plantations and coupling relationships among the components. Our analysis revealed that the C and N contents and C:P and N:P ratios of leaves, the P content of litter, and the C:N ratio of roots were the highest among all components. The seasonal dynamics showed that the N and P contents of leaves and roots and the P content of soil and litter were the highest in spring on all plantations, while the C:N, C:P and N:P of leaves, the C:N and C:P of roots and soil, and the C:P and N:P of litter were the lowest in spring. In all plantations, the N contents of BP and PR in each component were higher, while the P content and C:P and N:P ratios in roots of LR in summer were lower. The N element between litter-soil-root-leaf had a strong coupling relationship, and the P element between leaf-litter-root had a strong coupling relationship. Our results demonstrated that plants and the environment in each season on the Loess Plateau were mainly coupled and regulated by the N element in litter-soil-root-leaf and by the P element in leaf-litter-root. The plants absorbed N mainly from the soil and P mainly from litter. Plantations were limited by N in spring and summer and by P in autumn; this information may help guide plantation restoration and management.